STUDI POTENSI PENGEMBANGAN WISATA PANTAI MATRAS - Aqila, Nabila Safa; Herlambang, Suryono; Rahardjo, Parino (Jurusan Arsitektur dan Perencanaan, 2024)
Bangka Belitung Province is one of the provinces in Indonesia that is famous for its natural beauty, especially its beautiful beaches and has a stretch of white sand and is often visited by local and foreign tourists. The tourism sector is one of the sources of regional income. Matras Beach is one of the popular beaches in bangka district that is visited by many. Matras Beach has a length of 1.3 km with an existing land area of 19 Ha and a planning area of 23 Ha which is located in Matras Village, Sungailiat District, bangka district. Matras Beach is easily accessible to tourists and has natural potential such as freshwater streams, vegetation and white sand beaches that can be utilized as attractions. However, the physical condition also has several problems such as abrasion and tin mining activities in Matras Beach waters which often affect water quality and the beach area is still not well managed due to the lack of provision of facilities, facilities, infrastructure such as parking lots and also interesting activities on the beach still do not exist. Therefore, the purpose of this study is to determine the natural potential of Matras Beach and the arrangement of Matras Beach in order to make Matras Beach more organized, have attractiveness, provide adequate infrastructure facilities and have activity attractions that are in accordance with the standards and interests of Matras Beach tourists. Keywords: beach; facilities; infrastructure; recreation Abstrak Provinsi Bangka Belitung merupakan salah satu provinsi di Indonesia yang terkenal dengan keindahan alamnya, terutama pantai-pantainya yang indah serta memiliki hamparan pasir putih dan kerap dikunjungi oleh wisatawan lokal maupun wisatawan asing. Sektor pariwisata menjadi salah satu sumber pendapatan daerah. Pantai Matras merupakan salah satu pantai popular di Kabupaten Bangka yang banyak sekali dikunjungi. Pantai Matras memiliki panjang mencapai 1,3 km dengan luas lahan eksisting 19 Ha dan luas perencanaan 23 Ha yang terletak di Kelurahan Matras, Kecamatan Sungailiat, Kabupaten Bangka. Pantai Matras mudah diakses oleh wisatawan dan memiliki potensi alam seperti aliran air tawar, vegetasi serta pesisir pasir putih yang bisa dimanfaatkan sebagai daya tarik. Namun, pada kondisi fisiknya juga memiliki beberapa permasalahan seperti abrasi dan aktivitas pertambangan timah pada perairan Pantai Matras yang kerap mempengaruhi kualitas air serta kawasan pantai masih belum dikelola dengan baik karena kurangnya penyediaan fasilitas, sarana, prasarana seperti lahan parkir dan juga aktivitas menarik yang ada pada pantai tersebut masih belum ada. Maka dari itu, tujuan dari penelitian ini mengetahui potensi alam Pantai Matras dan mengajukan rekomendasi penataan Pantai Matras agar menjadikannya lebih tertata, memiliki daya tarik, memiliki fasilitas sarana prasarana yang mencukupi, serta memiliki atraksi aktivitas yang sesuai dengan standar dan minat dari wisatawan Pantai Matras.